Graphene filled optical fiber Fabry‐Pérot cavity tunable filter. Issue 11 (25th June 2019) - Li, Lijun; Shi, Zhihui; Liu, Yinming; Liu, Qian; Ma, Yanhua; Xu, Tianzong; Sun, Jianhong
Abstract: Before saturated absorption, graphene possesses optical nonlinear refractive index, which is a photoinduced refractive index effect. Taking advantage of this effect, a wavelength tunable filter is realized based on a graphene filled all optical fiber Fabry‐Pérot microcavity. Experimental results show that the interference wavelength of the filter exhibits linear red‐shift with the increase of the tunning optical power and tunning efficiency increases with the increase of cavity length and filled graphene thickness. In this study, the maximum wavelength vs power tunning efficiency can get 66 pm/mW. This filter has the advantages of high tunning efficiency, simple structure, antienvironmental interference good mechanical performance, and repeatability.